Characteristics of internal porosity of cork container media - Ordovas, J.; Carmona, E.; Moreno, M. T.; Ortega, M. C. (HORTSCIENCE, 1996)
The structure of cork (Quercus suber L.) bark presents a series of characteristics, suggesting that internal porosity is partly occluded. This study determined the porosity in the waste cork industry (C) and when such waste product had been composted during 4 (CC-4), 7 (CC-7), and 10.5 months (CC-10.5). The particle density of the intact and finely ground material differed significantly in all particle size ranges larger than 0.5 mm. The porosity of the cork substrates ranged from 80% to 94% of the total volume, according to granulometry and the degree of decomposition. However, large particles and less decomposed material with a high porosity had up to 10% of the total volume as occluded pores. The material's effective porosity varied slightly between the various particle sizes and degrees of decomposition, which ranged between 80% and 89%, having an average value of 85%. The ash content was highly correlated with the particle density of the finely ground material. Nevertheless, and due to occluded porosity, we cannot estimate the `'effective porosity'' from the ashes; therefore, we must resort to techniques that involve the displacement of a fluid, such as liquids or gas pycnometry or submersion.
The following values have no corresponding Zotero field: pub-location: 701 NORTH SAINT ASAPH STREET, ALEXANDRIA, VA 22314-1998 publisher: AMER SOC HORTICULTURAL SCIENCE
Keywords: ash content; effective porosity; particle density; total porosity